Variations of wellbeing measures between player`s participation in a match and a playing position: a study of youth soccer players - Pastor-Vicedo, J. C.; Clemente, F. M.; González-Fernández, F. T.; González-Villora, S. (Journal of Physical Education and Sport, 2023)
Soccer is a sport characterized by combining high-intensity actions with low-intensity actions. This makes it a complex sport, where monitoring the impact of actions that occur both in training and in matches are of great interest to coaches. However, this interest has focused on physical and physiological demands, and not so much on more psychological components. The aim of the study was analysing variations of wellbeing (i) between different match participation profiles and (ii) between playing positions. Twenty under-23 professional male soccer players (20.6±1.0 years) were monitored over a season. The scores were collected before the daily training session or match day. Two hundred training sessions and 38 competition matches were applied throughout the season. An adjusted version of the Hooper questionnaire was used to monitor the wellness in which muscle soreness, fatigue, stress, and mood were measured. Repeated-measures analysis of variance was executed to test the wellness and contextual factor. Bonferroni`s post hoc test was used to performed differences between groups. Results revealed that measures were modified by player participation (p = .00) and player position on the field (p = .00). Reserves and starters had lower values of muscle soreness (p = .62; ES = 0.18) and fatigue (p =.21; ES = -0.25) also reserves showed the worst values of stress (p = .00; ES= 0.38-0.58). Forwards and defenses presented worse values than midfielders and goalkeepers for all items registered (all p < .05). The results allow us to suggest that both contextual factors play an important role in the well-being variables reported the week after the match. Therefore, practitioners should consider them for managing training stimulus and recovery strategies.